Delivering successful presentations (American Management Association, 1992)
Learn how to prepare, practice, and deliver convincing presentations with this exciting new edition to the American Management Association's award-winning FYI Video Series. Delivering Successful Presentations shows step-by-step the proven tips and techniques that effective, successful presenters use to make their point. You watch successful presenters in action. You'll hear them describe their meticulous preparation, the insentive rehearsals, and their anticipation as they stand to deliver. In just thirty minutes you can learn the stand-up skills you need to make your presentations effective, convincing, and successful.